Taxonomic Review of the Subtribe Athouina Candèze, 1859 (Coleoptera, Elateridae, Dendrometrinae, Dendrometrini) in Korea - Han, Taeman; Park, Haechul; Lee, Youngbo; Kim, Namjeong; Ôhira, Hitoo; Platia, Giuseppe; Lee, Seunghwan (Zootaxa, 2012)
In this revision of the subtribe Athouina of Dendrometrini, we recognized three species including Cidnopus nigronitidus sp. nov., Limonius scutellaris (Dolin, 2003) comb. nov., all new to Korea, and Limoniscus kraatzi (Candèze, 1879) is recognized as the most abundant species in the Korean Peninsula. Previous records of Athousius humeralis (Miwa, 1927) and Limoniscus rufipennis (Lewis, 1894) have been confirmed to be misidentifications of Ampedus basalis (Mannerheim, 1852) and Corymbitodes sp., respectively and the records of Limonius eximius (Lewis, 1874) and Limoniscus vittatus (Candèze, 1873) are also questionable because no specimens are known from the Korean Peninsula.